Evaluation of the Implementation of the Principal Inspectorate’s Role of Agency X in the Performance Audit - Khairunnisa; Dyah Setyaningrum (Universitas Hayam Wuruk Perbanas, 2025)
A gap exists between the Regulation of the Financial and Development Supervisory Agency (BPKP) Number 8 of 2021 and the implementation of the Principal Inspectorate’s role of Agency X in the Performance Audit of Activity X. In contrast, the agency’s target to achieve capability level 4 within the next four years underscores the importance of research that aims to evaluate the implementation of the role of Irtama of Agency X in the Performance Audit of Activity X based on BPKP Regulation Number 8 of 2021 and to provide recommendations for improvement to enhance its capability level to level 4. The research employs a qualitative evaluation case study approach. Secondary data were obtained from qualitative document instruments, while primary data were collected through interviews and questionnaires. It examines the perspectives of auditors, auditees, and BPKP evaluators. The results indicate that Irtama of Agency X implemented only 9 of 16 statement fulfillment items at Level 3 (56.25%) and none at Level 4 (0%). The implications suggest that Agency X should promptly develop a risk management framework, and the Principal Inspectorate of Agency X should prepare its annual plan based on Agency X’s risk management, revise the performance audit guidelines, and ensure that the performance audit results generate 3E findings.